2022
DOI: 10.58567/jea01020002
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Heterogeneity of Green Biased Technology Progress in Chinese Industries: Decomposition Index Analysis Based on the Slacks-based measure integrating

Abstract: Green biased technological progress takes into account the influence of energy input and pollution emission, which is of great significance to China's green development. This paper decomposes technological progress into green input biased technological progress (IBTC) and green output biased technological progress (OBTC) using the Slacks-based measure integrating (SBM) model. Factor bias in technological progress is determined based on data from 34 industries in China from 2000 to 2015. The results show that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Therefore, the Chinese government has firmly advocated that innovation is key strategic foundation for building a modern economic system (Tu et al 2023 ). Technological innovation, as the primary source of economic growth, plays a crucial role in enhancing local productivity, while also acting as the fundamental driving force in the overall progress of national economic development (Wu et al 2021 ; Fan et al 2022 ; Meng et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the Chinese government has firmly advocated that innovation is key strategic foundation for building a modern economic system (Tu et al 2023 ). Technological innovation, as the primary source of economic growth, plays a crucial role in enhancing local productivity, while also acting as the fundamental driving force in the overall progress of national economic development (Wu et al 2021 ; Fan et al 2022 ; Meng et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, when economic development reaches a certain level, an environmentally sustainable economic development state will be formed due to the factors of low-carbon technology and environmental policies (Kaika and Zervas 2013 ). Meng et al ( 2022 ) factor bias in technological progress is determined based on data from 34 industries in China from 2000 to 2015. They found that China first tends to consume energy to pursue capital between capital input and energy input, while it tends to save energy after the Eleventh Five-Year Plan.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the current research is deficient in two aspects. Environmental issues have been a hot topic and scholars have been active in verifying the impact of different policies on it (Liu et al, 2022;Wu et al, 2021;Meng et al, 2022;Cheng et al, 2022). The number of studies that specifically focus on the relationship between urbanization and cultivated land is limited.…”
Section: Literature Reviewmentioning
confidence: 99%